Aerosol and Droplet Risk of Common Otolaryngology Clinic Procedures. (November 2021) - Boorgu, Devi Sai Sri Kavya; Dharmarajan, Harish; Sim, Edward S.; Goyal, Lindsey; Freiser, Monika E.; Weinstock, Michael; Whelan, Rachel; Corcoran, Timothy E.; Jabbour, Noel; Wang, Eric; Chi, David H.
Objectives: Define aerosol and droplet risks associated with routine otolaryngology clinic procedures during the COVID-19 era. Methods: Clinical procedures were simulated in cadaveric heads whose oral and nasal cavities were coated with fluorescent tracer (vitamin B2) and breathing was manually simulated through retrograde intubation. A cascade impactor placed adjacent to the nares collected generated particles with aerodynamic diameters ≤14.1 µm. The 3D printed models and syringes were used to simulate middle and external ear suctioning as well as open suctioning, respectively. Provider's personal protective equipment (PPE) and procedural field contamination were also recorded for all trials using vitamin B2 fluorescent tracer. Results: The positive controls of nebulized vitamin B2 produced aerosol particles ≤3.30 µm and endonasal drilling of a 3D model generated particles ≤14.1 µm. As compared with positive controls, aerosols and small droplets with aerodynamic diameter ≤14.1 µm were not detected during rigid nasal endoscopy, flexible fiberoptic laryngoscopy, and rigid nasal suction of cadavers with simulated breathing. There was minimal to no field contamination in all 3 scenarios. Middle and external ear suctioning and open container suctioning did not result in any detectable droplet contamination. The clinic suction unit contained all fluorescent material without surrounding environmental contamination. Conclusion: While patients' coughing and sneezing may create a baseline risk for providers, this study demonstrates that nasal endoscopy, flexible laryngoscopy, and suctioning inherently do not pose an additional risk in terms of aerosol and small droplet generation. An overarching generalization cannot be made about endoscopy or suctioning being an aerosol generating procedure. Level of Evidence: 3